Perancangan dan Evaluasi Aplikasi Mobile Berbasis Pengguna untuk Pengelolaan Sampah Berbasis Komunitas - Asyrafil Anam, Maulana; Supriyanto (SOTVI - Society of Visual Informatics, 2025)
It is very hard to keep an eye on garbage at the village level when there is no clear information about when sorted waste will be picked up and when sales will happen, and when there is no method for documenting waste data. This lack can cause garbage to build up in places where it shouldn't and make it harder to manage waste properly. To fix these problems, Badan Usaha Milik Kalurahan needs a mobile app that is easy to use and makes waste management tasks easier. BUMKALs are very important for helping communities grow and providing important services, like trash management. This study is all about making a trash management software, with a big focus on User Interface and User Experience principles. The design process uses a User-Centered Design method, which makes sure that users are included in every step. This method makes sure that the final application fits their demands and wants very well. In Caturharjo Village, which is in the Pandak Subdistrict of Bantul Regency, the local BUMKAL has taken the lead in starting community-based garbage management. But they still have problems with keeping track of data in a systematic way and having good ways to communicate. We used the User Experience Questionnaire to find out how users felt about the design of the program and how satisfied they were with it. The evaluation results show that the mobile app had mostly good feedback on all UEQ aspects, such as how clear, beautiful, and useful it was. All of the ratings were over the positive benchmark, which is really impressive. This shows that users were very happy with the application that was made, which means it may be successfully implemented and used.